Exome sequencing of pashtun familial epilepsy in Pakistan reveals novel variants in LAMA5, KCNQ2 and GNAO1 - Qaisar Ali; Sadiq Azam; Jamila Javed; Muhammad Zaheer; Saqib Ullah; Aqib Iqbal; Ibrar Khan; Shoaib Ur Rehman (Molecular Biology Reports, 2026)

NLRP1 gene polymorphism rs2670660 is associated with vitiligo in the Pakistani population - Sehresh Murtaza; Nasir Masood; Maleeha Azam; Muhammad Ajmal (Molecular Biology Reports, 2026)

Multiplexed CRISPR/Cas9 mediated knockdown of BCH gene in potato enhances beta-carotene to combat vitamin A deficiency - Ujala Nasir; Aneela Yasmeen; Muhammad Awais; Ayesha Latif; Allah Bakhsh; Nadeem Ahmad; Naila Shahid; Saira Azam; Abdul Qayyum Rao; Ahmad Ali Shahid (Plant Science, 2026)

Genome-wide study uncovering the role of GPAT gene family in watermelon and functional validation of ClGPAT8 against cold stress - Ali Aslam; Xiaomeng Wang; Muhammad Waseem; Muhammad Azam; Ashir Masroor; Qinghua Shi; Sher Muhammad; Aseel Smerat; Muhammad Khuram Razzaq; Ruimin Zhang (Plant Science, 2026)

Uncovering the central role of GhSPL13 in vegetative growth, root architecture, and stress responses in cotton - Sahar Sadaqat; Muhammad Awais; Muhammad Saad bin Tahir; Ramsha Ajmal; Aneela Yasmeen; Saira Azam; Naila Shahid; Ayesha Latif; Allah Bakhsh; Ruhangiz Mammadova; Abdul Qayyum Rao (Plant Science, 2026)

Sensors and smart food packaging for supply chains: Bridging expiration dates and actual perishability - Muhammad Umar Azam; Jolina Rodrigues; Mohamed Hamid Salim; Sarath Haridas Kaniyamparambil; Khalid Askar; Imane Belyamani; Blaise L. Tardy; Nouha Alcheikh (Food Control, 2026)

Highly selective solar CO2 conversion into ethanol over metal-free sulfonated g-C3N4/nitrogen doped reduced graphene oxide hybrid photocatalyst - Sachin G. Ghugal; Amol U. Pawar; Park Kyoung Mo; Poonchi Sivasankaran Ramesh; Harish Reddy Inta; Sanjeev Gupta; Sung-hoon Oh; Muhammad Zaeem Azam Khan; Young Seok Son; Hyunchul Shin; Hongxian Han; Young Soo Kang (Chemical Engineering Journal, 2026)

A review of piezoelectric sensor applications for structural health monitoring in automotive suspension systems - Saqlain Abbas; Saim Haider; Zahid Hussain; Afraz Khalid; Zulkarnain Abbas; Xiaotong Tu; Muhammad Ahtisham; Saira Azam (Next Research, 2026)

Bio-VegeGrout for soil strength enhancement: Effects of fermentation period on mechanical performance and microstructural characteristics - Wan Aisyah Fadilah Wae AbdulKadir; Rohayu Che Omar; Simon Gregory; Farah 'Atiqah Abdul Azam; Megan Barnett; Muhammad Afiq Mohamed Akbar; Nur 'Atikah Mahazir (Bioresource Technology Reports, 2026)

Exogenous salicylic acid induces GluA and PR1a defense genes and enhances tomato tolerance to combined salinity and bacterial canker stress - Jawad Ahmad; Hammad Ahmed Abbasi; Muhammad Atif; Sana Ullah; Abdullah Jalal; Zunaira Azam; Hafsa Bibi (Vegetos, 2026)

Mineralogical and microstructural characterization of lithium-bearing ore from Gilgit-Baltistan, Pakistan - Muhammad Yousif; Jehanzaib Anwar; Razia Kalsoom; Ammarah Kanwal; Muhammad Azam; Muhammad Afzal; Farooq Ahmed; Syed Hussain Imam Abidi (Arabian Journal of Geosciences, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Regional cryosphere strategy for the Hindu Kush Himalaya - Sher Muhammad; Mohd. Farooq Azam; Miriam Jackson; Qianggong Zhang (Journal of Mountain Science, 2026)
The Hindu Kush Himalaya (HKH) hosts the largest concentration of glaciers, seasonal snow, and permafrost outside the polar regions. Ongoing climate change has accelerated glacier mass loss, reduced snow cover, degraded permafrost, and altered runoff seasonality. These changes have amplified multihazard risks such as glacial lake outburst floods, avalanches, and landslides, with cascading impacts on water, energy, food, ecosystems, and livelihoods. Yet, field monitoring remains sparse, fragmented, and uneven across the region with limited long-term records and minimal data sharing. This perspective presents a Regional Cryosphere Strategy (RCS) for the HKH that responds to these deficits by: (i) consolidating and institutionalising standardised monitoring of glaciers, snow, and permafrost; (ii) building sustained capacity through specialised regional capacity-building activities, fellowships, and shared instrumentation with priority given to a Gender Equality and Social Inclusion (GESI) framework; (iii) establishing a Regional HKH CryoHub to ensure Findable, Accessible, Interoperable, and Reusable (FAIR) and policy-relevant data and knowledge services; and (iv) prioritising operational decision-support services such as the HKH seasonal Snow Watch for water and energy planning, hazard monitoring and early warning systems, and basin-scale assessments that link cryosphere trends to risks for people and infrastructure. This strategy is designed to align HKH observations and services with global initiatives, ensuring that regional data streams inform global assessments while countries can access technical and financial support mechanisms. We argue that a basin-representative, quality-assured, and interoperable cryosphere observation and services system can strengthen regional resilience, reduce risks, and amplify the HKH voice in global climate dialogues.

In-situ synthesis of ZIF-8@GO composites for efficient aqueous dye removal: a systematic study of performance and reusability - Khushboo Iman; Muhammad Umar Azam; Khalid Askar; Nouha Alcheikh; Rana Sabouni (Environmental Science and Pollution Research, 2026)

Plant viruses as next-generation vectors for transgene-free genome editing, gene regulation, and rapid crop improvement - Abdul Ali Azam; Muhammad Salman Iqbal; Huma Saleem; Revocatus Bahitwa; Hai Wang (Plant Molecular Biology, 2026)

Integrated hydrochemical and health-risk assessment of fluoride and major ions in groundwater from hattar and gadoon industrial estates, pakistan - Tofeeq Ahmad; Anwar Qadir; Muhammad Azam Khan; Nabeel Akhtar; Alaa Ahmed (Environmental Geochemistry and Health, 2026)

Human development under environmental and socioeconomic pressures: an ARDL-based assessment of life expectancy in Pakistan - Muhammad Khalid Anser; Muhammad Imran; Helmi Ali Mkaouar; Jameel Ahmad Khader; Alaa Shoukry; Wasfi Yengui; Kamran Azam; Khalid Zaman (Air Quality, Atmosphere & Health, 2026)

Acacia (Acacia nilotica) seed oil-based nanoemulsion delays softening of mango fruit by modulating oxidative stress and suppressing cell wall degradation - Shaghef Ejaz; Abdul Manan Abbas; Sajid Ali; Muhammad Azam; Mehdi Maqbool; Muhammad Saqib; Muhammad Abid (Journal of Stored Products Research, 2026)

Valorization of recycled concrete fine aggregates in gypsum mortars for developing eco-friendly false ceiling plates - Rashid Latif; Muhammad Rizwan Riaz; Anam Fatima; Rizwan Azam; Muhammad Hassan Javed (Innovative Infrastructure Solutions, 2026)

Unraveling survival disparities in primary central nervous system (CNS) lymphoma: an analysis of race, socioeconomic factors, and treatment outcomes using the surveillance, epidemiology, and end results program (2000–2021) - Shahzaib Maqbool; Mohammad Ebad Ur Rehman; Ramesha Tahir; Hafsa Arshad Azam Raja; Mouzma Ali; Muhammad Ibrahim; Jacob Guerrero; Abdur Rehman; Imran Khan; Abat Khan; Jose D. Sandoval-Sus (Cancer Causes & Control, 2026)

Intelligent microfluidics: A deep learning-integrated platform for high-accuracy oocyte membrane permeability characterization in cryobiology - Kashan Memon; Bing Zhang; Muhammad Azam Fareed; Lingxiao Shen; Zhicheng Liu; Gang Zhao (Analytica Chimica Acta, 2026)

Role of Nano-Silicon, Nano-Biochar, and Irrigation Strategies in Managing Tellurium Toxicity: Implications for Soil Microbiota, Wheat Yield, and Food Safety - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Zeeshan Ahmed; Rehman Habib; Javed Iqbal; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Gastroprotective effect of Kahweol against ethanol-induced gastric ulcer by employing in silico, in vitro and in vivo approaches - Shahid Khan; Abdul Qadir; Jawad Azam; Muhammad Noman; Nadeem Ahmad; Zaheer Ul-Haq; Kashif Bashir; Tajamul Hussain; Salman Alrokayan; Muhammad Latif; Hussain Ali; Yousaf Kamal; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction Note: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2026)

Synergistic effects of foliar selenium nanoparticles and aged cellulose-derived biochar on PAH immobilization and spinach health in contaminated soils - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Zeeshan Ahmed; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Environmental Geochemistry and Health, 2026)

Physics informed kriging convolutional graph attention network for predicting minimum horizontal stress from seismic attributes and finite element simulations - Muhammad Azam Khan; Yang Zhao; Mandella Ali M. Fargalla; Wyclif Kiyingi; Chenggang Xian; Chunduan Zhao; Liang Xing (International Journal of Rock Mechanics and Mining Sciences, 2026)

TrIFS strengthens isoflavonoid accumulation and improves aluminum tolerance involved with GmALDH22A2-GmRBOHL pathway in soybean - Biao Wang; Shoufeng Cheng; Cunhao Yu; Muhammad Azam; Qingshan Chen; Tianlong Wu; Mingzhe Zhao; Xiaohong Ma; Luming Yao (Journal of Hazardous Materials, 2026)

Corrigendum to ‘Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads’ [International Journal of Refrigeration 181 (2026) 111–125] - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

Performance comparison and sustainability assessment of mesoporous FAU zeolites for the plastic upcycling - Muhammad Usman Azam; Nanbyen George Kim; Auguste Fernandes; M. Filipa Ribeiro; Waheed Afzal; Inês Graça (Chemical Engineering Journal, 2026)

Navigating climate policy uncertainty: how innovation and institutional quality drive GHG emissions reduction in G7 countries - Muhammad Asif; Muhammad Azam Zia; Mughair Aslam Bhatti (Clean Technologies and Environmental Policy, 2026)

Identification of a biallelic MMUT variant (p.Thr230Arg) and its global perspective on clinical management - Sumreena Mansoor; Qamar Ali; Sabeen Abid Khan; Munir Iqbal Malik; Muhammad Imran; Raheel Qamar; Maleeha Azam (Molecular Biology Reports, 2025)

Evaluation of Agronomic Traits and Bioactive Compounds in Five Mentha Species Under Soil-Based and Hydroponic System - Muhammad Azam Khan; Ismara Naseem; Muhammad Tahir Akram; Umer Habib; Rashid Mehmood Rana (Journal of Soil Science and Plant Nutrition, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Mechanical characterization and impact resistance of concrete incorporating recycled thin-walled hollow tubular GFRP sections - Muhammad Rizwan Riaz; Muhammad Moeed Azhar; Muhammad Fahad Ejaz; Rizwan Azam; Muhammad Faraz Javaid (Innovative Infrastructure Solutions, 2025)

Green technology, digital transformation, and energy efficiency: driving carbon reduction and waste management innovation in G20 Countries - Muhammad Asif; Muhammad Azam Zia; Muhammad Hashim; Uzair Aslam Bhatti (Clean Technologies and Environmental Policy, 2025)

Circular Economy in Oilfield Systems: A Review of Culinary Waste Materials for Sustainable Drilling Fluids - Muhammad Hammad Rasool; Syahrir Ridha; Maqsood Ahmad; Numair Ahmed Siddiqui; Muhammad Khurram Zahoor; Azam Khan; Syed Abdul Moiz Hashmi (Circular Economy and Sustainability, 2025)

Mitigating Fruit Drop Challenges: Unraveling the Role of Plant Growth Regulators and Micronutrients in Jujube (Ziziphus mauritiana L.) cvs. in the Cholistan Desert, Pakistan - Abdul Haseeb Ahmed; Rashad Qadri; Khalid Hussain; Muhammad Tahir Akram; Muhammad Azam; Muhammad Awais Ghani; Muhammad Mumtaz Khan; Muhammad Asif Rai; Basharat Ali; Abd El-Zaher M. A. Mustafa; Mohamed S Elshikh; Ghulam Murtaza; et al. (Applied Fruit Science, 2025)

Morpho-molecular diversity and host range dynamics of squash powdery mildew pathogens prevailing in Pothwar Plateau, Pakistan - Beenish Gul; Farah Naz; Mathews L. Paret; Fanny Iriarte; Zain Haider; Gulshan Irshad; Muhammad Azam Khan (Journal of Plant Pathology, 2025)

Submergence stress in plants: molecular mechanisms, physiological changes, and adaptive responses - Noreen Iftikhar; Muhammad Saad Bhutta; Narmeen Tariq Zaman; Ayesha Khalid; Ayesha Latif; Saira Azam; Naila Shahid; Aneela Yasmeen; Abdul Qayyum Rao (Physiology and Molecular Biology of Plants, 2025)

Corrigendum to “Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite” [J. Environ. Chem. Eng. 9 (2021) 104919] - Shahid Iqbal; Naveed Ahmad; Mohsin Javed; Muhammad Azam Qamar; Ali Bahadur; Shahid Ali; Zahoor Ahmad; Rana Muhammad Irfan; Guocong Liu; Muhammad Bilal Akbar; Muhammad Abdul Qayyum (Journal of Environmental Chemical Engineering, 2025)

Leveraging transfer learning for data-driven proton exchange membrane fuel cells using surrogate models - Sadia Siddiqa; Kyoungsik Chang; Sahrish Batool Naqvi; Muhammad Azam; Md. Mamun Molla; Khanh-Hoan Nguyen (Fuel, 2025)

Non-linear complementarity model including large displacements and strain rate effects for RC beams under impact - Muhammad Anas; Haseeb Ahmed; Azam Khan; Mudassir Arshad; Moiz Tariq (Engineering Structures, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Quantitative Analysis of Pesticide Residues in Guava (Psidium guajava L.) Fruit by Using High Performance Liquid Chromatography - Rashad Qadri; Abdul Haseeb Ahmed; Muhammad Umair Ashraf; Muhammad Tahir Akram; Khalid Hussain; Muhammad Azam; Muhammad Imran Khan; Muhammad Mumtaz Khan (Applied Fruit Science, 2025)

Evaluating the Impact of Triacontanol on Physiological, Enzymatic and Biochemical Responses of Psidium Guajava L. Under Salinity Stress - Khalid Hussain; Rashad Qadri; Rashid Iqbal Khan; Abdul Haseeb Ahmed; Muhammad Azam; Muhammad Tahir Akram; Muhammad Imran Khan; Aneeqa Arshad; Swati Shrestha (Applied Fruit Science, 2025)

Facile construction of chitosan-ternary metal selenide biopolymer-based composite for photocatalytic degradation of petroleum derive sunset yellow and acid black azo-dyes using response surface methodology RSM - Tariq Aziz; Muhammad Farhan; Adnan Khan; Nisar Ali; Javeed Azam; Sumeet Malik; Sarmad Ali; Nauman Ali; Hamayun Khan; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; Thuraya Al-Harthy (Environmental Science and Pollution Research, 2025)

Molecular characterization of lumpy skin disease virus in the cattle population of District Lower Chitral, Khyber Pakhtunkhwa, Pakistan - Almas Faryal Nizam; Iram Maqsood; Hanif Ur Rahman; Saira Awaz; Imran Ullah Shah; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Asima Azam; Ayesha Hidayat (Antonie van Leeuwenhoek, 2025)

Corrigendum to “Application of nanomaterials for enhanced production of biodiesel, biooil, biogas, bioethanol, and biohydrogen via lignocellulosic biomass transformation” [Fuel 315 (2022) 122840] - Mehvish Mumtaz; Zulqarnain Baqar; Nazim Hussain; Afifa; Muhammad Bilal; Hafiz Muhammad Husnain Azam; Qurat-ul-ain Baqir; Hafiz M.N. Iqbal (Fuel, 2025)

Salicylic acid-induced defense responses against a newly identified cotton pathogen, Pantoea vagans - Muneeb Anwer; Muhammad Waqas Azam; Muhammad Taimoor Shakeel; Anam Moosa; Hongwei Zhao; Muhammad Aslam Farooqi; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi; Huda Alghamdi; Ambreen Maqsood; Muhammad Naveed Aslam (Physiological and Molecular Plant Pathology, 2025)

Synergistic Effects of 5-Ureidohydantoin, Rhizobacteria and Non-wood-Based Biochar on Barley Productivity Under Drought and Multiple Toxic Metals Stress - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Abdul Razzaq; Iram Saba; Gang Deng; Zeeshan Ahmed; Abdel-Rhman Z. Gaafar; Trobjon Makhkamov; Lala Gurbanova; Rashid Iqbal (Current Microbiology, 2025)

Exploration and evaluation of antioxidant activity in isolated phenolics from Jasminum scandens (retz) vahl - Afsin Malik; Faria Mannan Mithi; Sania Ashrafi; Muhammad Abdullah Al-Mansur; Monira Ahsan; Choudhury Mahmood Hasan; A.T.M. Zafrul Azam (Natural Product Research, 2025)

Development and structural performance evaluation of consistent-sized interlocking clay bricks as an alternative to conventional bricks: an experimental investigation - Muhammad Numan; Muhammad Rizwan Riaz; Rizwan Azam; Muhammad Faraz Javaid; Mohamed Zawam (Innovative Infrastructure Solutions, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Endophytes of Zingiberaceae: distribution and bioactivity of their bioactive metabolites - Nor Hazwani Mohd Hasali; Muhammad Shahbaz; Jaya Seelan Sathiya Seelan; Nazirul Azam Ibrahim; Christophe Wiart; Nivaarani Arumugam; Mohammed Abdus Salam; Muneeb M. Musthafa; Suganthi Appalasamy (Archives of Microbiology, 2025)

Exploring the synergies between natural resources, technological innovation, and fiscal and monetary policies for promoting environmental sustainability in ASEAN countries - Muhammad Azam Khan; Salma Zahir; Nor Salwati Othman; Abdul Majid Awan (Environment, Development and Sustainability, 2025)

Effects of neem leaf extract on physiochemical traits and antioxidant activity of peach fruit during storage - Jianhui Li; Muhammad Hanif; Muhammad Azam; Muhammad Arslan Khan; Muhammad Ali Umer; Beenish Chaudhary; Imtiaz Hussain; Tariq Aziz Khan; Shoaib ur Rehman; Muhammad Awais; Riadh Ilahy; Hongru Liu; et al. (Journal of Stored Products Research, 2025)

Is There Any Role of Zinc and Copper in Severity and Progression of Osteoarthritis? A Review - Umaima Cheema; Meeram Noor; Hurain Naeem; Mahnoor Arfan; Abdul-Rehman Azam; Shamikha Cheema; Hafiz Muhammad Haris; Muhammad Raza (Biological Trace Element Research, 2025)

Biomonitoring and phytoremediation potential of Conocarpus erectus (Buttonwood) for mitigating air pollution from highway traffic - Akkasha Azam; Ummar Iqbal; Zartasha Usman; Muhammad Sharif; Muhammad Faisal Gul; Nargis Naz; Ifrah Nawaz; Farooq Ahmad (Chemosphere, 2025)

The sustainability challenge and social benefits of industrialisation in NICs - Irsa Azam; Yongsheng Guo; Mirza Muhammad Naseer (Resources Policy, 2025)

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Impacts of soiling on solar panel performance and state-of-the-art effective cleaning methods: A recent review - Nadia Shahzad; Naveed Hussain; Shayan Umar; Muhammad Farooq Azam; Tanzeela Yousaf; Adeel Waqas (Journal of Cleaner Production, 2025)

Transforming field crops with CRISPR/Cas: a new era in genome editing - Asif Mukhtiar; Athar Mahmood; Muhammad Azam Khan; Muaz Ameen; Jameel Mohammed Al-Khayri; Sameer H. Qari (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Morphological profiling and DNA barcoding revealed genetic diversity and phylogeny of Mentha species cultivated in Pakistan - Ismara Naseem; Muhammad Azam Khan; Umer Habib; Rashid Mehmood Rana; Muhammad Qasim; Mona S. Alwahibi; Rizwana Khanum; Muhammad Shafiq; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Green synthesized silicon dioxide nanoparticles (SiO2NPs) ameliorated the cadmium toxicity in melon by regulating antioxidant enzymes activity and stress-related genes expression - Muhammad Sanaullah Malik; Asad Rehman; Iftikhar Hussain Shah; Samiah Arif; Kai Nan; Yumeng Yan; Shiren Song; Muhammad Khalid Hameed; Muhammad Azam; Yidong Zhang (Environmental Pollution, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Optimization-based innovative approach for economical design of reinforced concrete isolated footings - Junaid Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mansoor Shakeel (Innovative Infrastructure Solutions, 2025)

Human Brucellosis in the Rural and Urban Population of Pakistan: Seroprevalence, Risk Factors, and Clinical Manifestations - Faisal Abbas; Shahzad Ali; Ali Muhammad; Asima Azam; Amira A. Moawad; Mohammad Ejaz; Anam Iftikhar; Maryam Dadar (Current Microbiology, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

FeS-based nanocomposites: A promising approach for sustainable environmental remediation – Focus on adsorption and photocatalysis – A review - Aqsa Nawaz; Aman Khalid; Wajeeha Qayyum; Rabia Bibi; Muhammad Azam Qamar; Muhammad Zahid; Ahmad Farhan; Manoj P. Rayaroth; Łukasz Cichocki; Grzegorz Boczkaj (Journal of Environmental Management, 2025)

Unlocking the structure-activity relationship of hierarchical MFI zeolites towards the hydrocracking of HDPE - Muhammad Usman Azam; Auguste Fernandes; Maria João Ferreira; Alan J. McCue; Inês Graça; Waheed Afzal (Fuel, 2025)

Development of growth curve and estimation of genetic parameters of Nili-Ravi buffalo calves from birth to one year of age through non-linear models - Asad Abbas; Atia Basheer; Moinina Nelphson Kallon; Numan Sharif; Heydar Ghiasi; Tariq Mehmood; Burhane Azam; Anjum Khalique; Muhammad Dawood; Imran Zahoor (Tropical Animal Health and Production, 2024)

Molecular characterization of Peste des petits ruminants virus (PPRV) in sheep and goats and risk factors associated with it in selected districts of Khyber Pakhtunkhwa-Pakistan - Saira Awaz; Iram Maqsood; Hanif Ur Rahman; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Imtiaz Ali Shah; Asima Azam; Ayesha Hidayat; Almas Faryal Nizam (Molecular Biology Reports, 2024)

Characterization of volatile profile from different coriander (Coriandrum sativum L.) varieties via HS-SPME/GC–MS combined with E-nose analyzed by chemometrics - Shouhui Wei; Lijuan Wei; Bojie Xie; Ju Li; Jian Lyu; Shuya Wang; Muhammad Azam Khan; Xuemei Xiao; Jihua Yu (Food Chemistry, 2024)

Resilience underground: Understanding earthworm biomass responses to land use changes in the tropics - Badrul Azhar; Peter van der Meer; Rutger F. Sterenborg; Muhammad Syafiq Yahya; Norhisham Razi; Maisarah Burhanuddin; Jasmijn Rookmaker; Nur Syarihah Sahimi; Welmoed van der Pal; Frisco Nobilly; Siti Aisyah Mohd Azam; Meriam Ubachs; et al. (Biological Conservation, 2024)

Challenges and opportunities for the application of digital twins in hard-to-abate industries: a review - Muhammad Azam Hafeez; Alberto Procacci; Axel Coussement; Alessandro Parente (Resources, Conservation and Recycling, 2024)

Environmental implications of migration: Worldwide insights - Jianjiang Shen; Muhammad Azam; Hong Jin; Ahmed Imran Hunjra (Journal of Environmental Management, 2024)

Emerging paradigms in two-dimensional materials: Classification, synthesis, and the role of defects in electrocatalysis for water splitting and oxygen reduction reaction - Muhammad Sajid; Muhammad Azam Qamar; Ahmad Farhan; Wajeeha Qayyum; Aman Khalid; Aqsa Nawaz; Shern-long Lee; Haq Nawaz (Journal of Environmental Chemical Engineering, 2024)

Self-templated formation of ZnNC microtube with high oxygen reduction reaction overpotential for Zn-based catalyst - Ayaz Mahsud; Muhammad Arif; Asif Mehmood; Mohammad Azam; Xiaobing Wang; Zongxian Yang; Zhansheng Lu (Journal of Environmental Chemical Engineering, 2024)

Regression-based prediction of flow-induced dominant vibrational frequencies in two-phase flow regimes - Muhammad Sohail; William Pao; Abdul Rahim Othman; Huzaifa Azam; Muhammad Rehan Khan (Ocean Engineering, 2024)

Developing a simple and efficient modeling solution for predicting key phenological stages of table grapes in a non-traditional viticulture zone in south Asia - Rizwan Rafique; Touqeer Ahmad; Muhammad Azam Khan; Mukhtar Ahmed; Gerrit Hoogenboom (International Journal of Biometeorology, 2024)

Solar Light Assisted Metal Selenide-Chitosan Nanoparticles from Structure Tailoring to Photocatalytic Mineralization of Selected Industrial Dyes - Javeed Azam; Muhammad Farhan; Adnan Khan; Tariq Aziz; Nauman Ali; Hamayun Khan; Sumeet Malik; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Evolution and Trends of Water Scarcity Indicators: Unveiling Gaps, Challenges, and Collaborative Opportunities - Zafar Hussain; Zongmin Wang; Haibo Yang; Muhammad Arfan; Wusen Wang; Muhammad Faisal; Muhammad Imran Azam; Muhammad Usman (Water Conservation Science and Engineering, 2024)

Physico-mechanical characterization of eco-friendly gypsum composites incorporating shredded surgical face masks - Muhammad Hassan Javed; Muhammad Rizwan Riaz; Rizwan Azam; Muhammad Kashif; Anam Fatima (Innovative Infrastructure Solutions, 2024)

Comparative Assessment of Bioactive Compounds, Fruit Quality Attributes and Sugar Profiling in Early Maturing Table Grape (Vitis Vinifera L.) Cultivars from Pothohar, Pakistan - Muhammad Tahir Akram; Rashad Qadri; Muhammad Azam Khan; Arif Atak; Mehwish Liaquat; Tanveer Hussain; Muhammad Mumtaz Khan; Muhammad Azam; Mahmood ul Hasan (Applied Fruit Science, 2024)

Factors determining water stress: do environmental distress, energy consumption and industrialization matter? - Muhammad Azam Khan; Ijaz Uddin; Nor Salwati Othman (Environment, Development and Sustainability, 2024)

Empirical testing of the environmental Kuznets curve: evidence from 182 countries of the world - Muhammad Azam; Zia Ur Rehman; Himayatullah Khan; Ilham Haouas (Environment, Development and Sustainability, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

The impact of geopolitical risk, institutional governance and green finance on attaining net-zero carbon emission - Ahmed Imran Hunjra; Muhammad Azam; Peter Verhoeven; Dilvin Taskin; Jiapeng Dai (Journal of Environmental Management, 2024)

Improving Multivariate Runoff Prediction Through Multistage Novel Hybrid Models - Muhammad Sibtain; Xianshan Li; Fei Li; Qiang Shi; Hassan Bashir; Muhammad Imran Azam; Muhammad Yaseen; Snoober Saleem; Qurat-ul-Ain (Water Resources Management, 2024)

Anti-inflammatory potential of some eudesmanolide and guaianolide sesquiterpenes - Shagufta Perveen; Azadeh Hamedi; Ardalan Pasdaran; Reza Heidari; Muhammad Shafiq ul Azam; Sobia Tabassum; Rashad Mehmood; Jiangnan Peng (Inflammopharmacology, 2024)

Health, environment, and sustainable development: evidence from panel data from ASEAN countries - Muhammad Azam; Faridul Islam; Salim Rashid (Air Quality, Atmosphere & Health, 2024)

Additive engineering enabled non-radiative defect passivation with improved moisture-resistance in efficient and stable perovskite solar cells - Muhammad Azam; Zhicheng Ke; Junsheng Luo; Zhongquan Wan; Ali Hassan; Chunyang Jia (Chemical Engineering Journal, 2024)

Alleviated lead toxicity in rice plant by co-augmented action of genome doubling and TiO2 nanoparticles on gene expression, cytological and physiological changes - Fozia Ghouri; Munazzam Jawad Shahid; Minghui Zhong; Muhammad Azam Zia; Sarah Owdah Alomrani; Jingwen Liu; Lixia Sun; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Green fabrication of copper nano-fertilizer for enhanced crop yield in cowpea cultivar: A sustainable approach - Muhammad Mustafa; Muhammad Azam; Haq Nawaz Bhatti; Amina Khan; Laiba Zafar; Abdul Malik Rehan Abbasi (Biocatalysis and Agricultural Biotechnology, 2024)

Cassia Angustifolia Primed ASCs Accelerate Burn Wound Healing by Modulation of Inflammatory Response - Saba Tasneem; Hafiz Ghufran; Maryam Azam; Amna Arif; Musab Bin Umair; Muhammad Amin Yousaf; Khurrum Shahzad; Azra Mehmood; Kausar Malik; Sheikh Riazuddin (Tissue Engineering and Regenerative Medicine, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

A practical tool for structural design optimization of steel frames: development and application for parametric analysis - Umair Ali; Rizwan Azam; Mansoor Shakeel; Muhammad Adil; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2024)

Therapeutic Role of Hemp (Cannabis sativa) Against Copper-Induced Toxicity in Labeo rohita and Cirrhinus mrigala - Azam Jan Afridi; Amina Zuberi; Ali Muhammad Yousafzai; Muhammad Kamran (Biological Trace Element Research, 2024)

An assessment of bilateral debt swap financing indispensable for economic growth and environment sustainability: a policy implication for heavily indebted countries - Umar Suffian Ahmad; Sadia Safdar; Muhammad Azam (Environmental Science and Pollution Research, 2023)

Engineering of Chlamydomonas reinhardtii chloroplast for mucosal immunotherapeutic against Newcastle disease virus - Sania Naeem; Naila Shahid; Mohsin Ahmad Khan; Saira Azam; Muhammad Saad Bhutta; Ayesha Latif; Aneela Yasmeen; Tahir Rehman Sami Ullah; Abdul Qayyum Rao; Kausar Malik (Journal of Applied Phycology, 2023)

A bacterial consortium and L-tryptophan boosted glyphosate removal, mungbean growth and physiology in contaminated soil - Qammar Farooq; Muhammad Imran Khan; Muhammad Hayder Ali; Safdar Bashir; Muhammad Azam; Rashad Qadri; Basharat Ali; Muhammad Dawood; Muhammad Iftikhar Hussain (Arabian Journal of Geosciences, 2023)

Prospects of recycling from end-of-life of Li-ion batteries on alleviating materials demand-supply gap in new electric vehicles in Asia - Muhammad Shafique; Muhammad Ateeq; Muhammad Rafiq; Anam Azam; Xiaowei Luo (Waste Management, 2023)

Unraveling the synergy of interface engineering α-MnO2/Bi2WO6 heterostructures and defective active sites for superdurable photocatalysis: Mechanistic insights into charge separation/transfer - Muhammad Arif; Ayaz Mahsud; Amjad Ali; Shipeng Liao; Jiawei Xia; Hai Xiao; Mohammad Azam; Tahir Muhmood; Zhansheng Lu; Yinjuan Chen (Chemical Engineering Journal, 2023)

Temperature variability during the growing season affects the quality attributes of table grapes in Pothwar—insight from a new emerging viticulture region in South Asia - Rizwan Rafique; Touqeer Ahmad; Muhammad Azam Khan; Mukhtar Ahmed (International Journal of Biometeorology, 2023)

The impact of CSR and green consumption on consumer satisfaction and loyalty: moderating role of ethical beliefs - Sohail Ahmad; Muhammad Irfan Shakir; Afshan Azam; Shahid Mahmood; Qingyu Zhang; Zaheer Ahmad (Environmental Science and Pollution Research, 2023)

Exogenous melatonin mitigates chilling injury in zucchini fruit by enhancing antioxidant system activity, promoting endogenous proline and GABA accumulation, and preserving cell wall stability - Sajid Ali; Aamir Nawaz; Safina Naz; Maratab Ali; Shaghef Ejaz; Muhammad Azam; Kashif Razzaq (Postharvest Biology and Technology, 2023)

Hydrocracking of surgical face masks over Y Zeolites: Catalyst development, process design and life cycle assessment - Muhammad Usman Azam; Auguste Fernandes; Inês Graça; Waheed Afzal (Fuel, 2023)

Expanding annotation of chemical compounds in hawthorn fruits and their variations in thermal processing using integrated mass spectral similarity networking - Qiang Lyu; Wanying Zheng; Qiyuan Shan; Lichuang Huang; Yiwen Wang; Lu Wang; Haodan Kuang; Muhammad Azam; Gang Cao (Food Research International, 2023)

RETRACTED ARTICLE: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2023)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

The pervasiveness of microplastic contamination in the gastrointestinal tract of fish from the western coast of Bangladesh - Marhaba Matluba; Md. Kawser Ahmed; K.M. Azam Chowdhury; Nasim Khan; Md. Asrafur Rahman Ashiq; Muhammad Saiful Islam (Marine Pollution Bulletin, 2023)

Role of ethnic conflicts, regularization and natural resource abundance in sustainable development - Muhammad Azam; Ahmed Imran Hunjra; Dilvin Taskin; Mamdouh Abdulaziz Saleh Al-Faryan (Resources Policy, 2023)

Identification of quantitative trait loci and candidate genes for seed folate content in soybean - Kwadwo Gyapong Agyenim-Boateng; Shengrui Zhang; Rongzhe Gu; Shibi Zhang; Jie Qi; Muhammad Azam; Caiyou Ma; Yecheng Li; Yue Feng; Yitian Liu; Jing Li; Bin Li; et al. (Theoretical and Applied Genetics, 2023)

Infant mortality rate and nonrenewable energy consumption in Asia and the Pacific: the mediating role of carbon emissions - Bosede Ngozi Adeleye; Muhammad Azam; Festus Victor Bekun (Air Quality, Atmosphere & Health, 2023)

Do demographic factors affect the environment? Empirical evidence from the Middle East and North African countries - Ilham Haouas; Muhammad Haseeb; Muhammad Azam; Zia Ur Rehman (Environmental Science and Pollution Research, 2023)

Revisiting the determinants of life expectancy in Asia—exploring the role of institutional quality, financial development, and environmental degradation - Ijaz Uddin; Muhammad Azam Khan; Muhammad Tariq; Farah Khan; Zilakat Khan Malik (Environment, Development and Sustainability, 2023)

Seasonal variability in the effect of temperature on key phenological stages of four table grapes cultivars - Rizwan Rafique; Touqeer Ahmad; Mukhtar Ahmed; Muhammad Azam Khan; Carol J. Wilkerson; Gerrit Hoogenboom (International Journal of Biometeorology, 2023)

Cottonseed oil: A review of extraction techniques, physicochemical, functional, and nutritional properties - Tahreem Riaz; Muhammad Waheed Iqbal; Shahid Mahmood; Iqra Yasmin; Ali Ahmad Leghari; Abdur Rehman; Anam Mushtaq; Khubaib Ali; Muhammad Azam; Muhammad Bilal (Critical Reviews in Food Science and Nutrition, 2023)

Membrane-processed honey samples for pollen characterization with health benefits - Nabila; Mushtaq Ahmad; Ashwaq T. Althobaiti; Wahid Ali; Khansa Masood; Mohamed Fawzy Ramadan; Bisha Chaudhary; Muhammad Zafar; Muhammad Saeed Akhtar; Shazia Sultana; Sasan Zahmatkesh; Tariq Mehmood; et al. (Chemosphere, 2023)

Plant-assisted synthesis and characterization of MnO2 nanoparticles for removal of crystal violet dye: an environmental remedial approach - Muniba Rahmat; Shumaila Kiran; Tahsin Gulzar; Mohd Yusuf; Rabia Nawaz; Javaira Khalid; Nooria Fatima; Ata Ullah; Muhammad Azam (Environmental Science and Pollution Research, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Decision tree regression algorithm-based model for prediction of traffic-induced vibrations: development and application for parametric investigation - Muhammad Faraz Javaid; Rizwan Azam; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2023)

Photocatalytic degradation and electrochemical energy storage properties of CuO/SnO2 nanocomposites via the wet-chemical method - Azam Khan; Inam Ullah; Afaq Ullah Khan; Bilal Ahmad; Khadijah Mohammedsaleh Katubi; Norah Salem Alsaiari; Muhammad Saleem; Mohd Zahid Ansari; Jianjun Liu (Chemosphere, 2023)

CRISPR/Cas9-mediated genome editing in diploid and tetraploid potatoes - Aneela Yasmeen; Allah Bakhsh; Sara Ajmal; Momna Muhammad; Sahar Sadaqat; Muhammad Awais; Saira Azam; Ayesha Latif; Naila Shahid; Abdul Qayyum Rao (Acta Physiologiae Plantarum, 2023)

Experimental design by response surface methodology for efficient cefixime uptake from hospital effluents using anion exchange membrane - Muhammad Ali Khan; Nadeem Raza; Suryyia Manzoor; Ramsha Shuja; Hina Raza; Muhammad Imran Khan; Mudassar Azam; Abdallah Shanableh (Chemosphere, 2023)

Recent Advances and Treatment of Emerging Contaminants Through the Bio-assisted Method: A Comprehensive Review - Abdul Sattar Jatoi; Jawad Ahmed; Faheem Akhter; Syed Haseeb Sultan; Ghulam Sever Chandio; Shoaib Ahmed; Zubair Hashmi; Muhammad Azam Usto; Muhammad Shuaib Shaikh; Muhammad Siddique; Ghulamullah Maitlo (Water, Air, & Soil Pollution, 2023)

Identification of genes for seed isoflavones based on bulk segregant analysis sequencing in soybean natural population - Muhammad Azam; Shengrui Zhang; Yuanyuan Huai; Ahmed M. Abdelghany; Abdulwahab S. Shaibu; Jie Qi; Yue Feng; Yitian Liu; Jing Li; Lijuan Qiu; Bin Li; Junming Sun (Theoretical and Applied Genetics, 2023)

Analysis of Temperature Data Using the Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar, Pakistan - Fiaz Hussain; Ray-Shyan Wu; Ghulam Nabi; Rana Shahzad Noor; Muhammad Naveed Anjum; Muhammad Azam; Arslan Afzal (Pure and Applied Geophysics, 2023)
The trend analysis approach is used to estimate changing climate and its impact on the environment, agriculture and water resources. Innovative polygonal trend analyses are qualitative methods applied to detect changes in the environment. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for temperature trend detection in Soan River Basin (SRB), Potohar region, Pakistan. The average monthly temperature data (1995–2020) for 11 stations were used to create polygon graphics. Trend length and slope were calculated separately for arithmetic mean and standard deviation. The innovative methods produced useful scientific information, with the identification of monthly shifts and trend behaviors of temperature data at different stations. Some stations showed an increasing trend and others showed decreasing behavior. This increasing and decreasing variability is the result of climate change. The winter season temperature is increasing, and the months of December to February are getting warmer. Summer is expanding and pushing autumn towards winter, swallowing the early period of the cold season. The monthly polygonal trends with risk graphs depicted a clear picture of climate change in the Potohar region of Pakistan. The phenomena of observed average temperature changes, indicated by both qualitative methods, are interesting and have the potential to aid water managers’ understanding of the cropping system of the Potohar region.

The determinants of life expectancy and environmental degradation in Pakistan: evidence from ARDL bounds test approach - Muhammad Azam; Ijaz Uddin; Najia Saqib (Environmental Science and Pollution Research, 2023)

Global declarations on electric vehicles, carbon life cycle and Nash equilibrium - Baher Bakhtyar; Zhang Qi; Muhammad Azam; Salim Rashid (Clean Technologies and Environmental Policy, 2023)
Universal environmental policies adopt strategies that enhance and encourage the production and usage of electric vehicles (EVs). Universal cooperation is evident in the framework of agreements or protocols so as to successfully lead countries towards the predetermined goals. The question is whether this trend can reduce global warming or CO 2 emissions worldwide. By adopting game theory, this study analyses electricity carbon life cycle in leading EV countries. Results show that although the spread of EVs in Europe and the USA can mitigate carbon emissions, the production and use of electric vehicles in some countries, such as China and India, become a new source of such emissions. This reverse effect is due to the emission of greenhouse gases from electricity sources in these countries. Game theory also suggests that countries with unclean electricity sources should reconsider their plans to produce and use EVs. This study confirms that although carbon emission and global warming are global problems, regional and local policies can be substituted with a single comprehensive approach for an effective means of CO 2 emission reduction. Graphical abstract

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Association mapping for abiotic stress tolerance using heat- and drought-related syntenic markers in okra - Ikhlaq Ahmad; Rashid Mehmood Rana; Mahmood Ul Hassan; Muhammad Azam Khan; Muhammad Sajjad (Molecular Biology Reports, 2022)

Are globalization, urbanization, and energy consumption cause carbon emissions in SAARC region? New evidence from CS-ARDL approach - Muhammad Azam; Ijaz Uddin; Saleem Khan; Muhammad Tariq (Environmental Science and Pollution Research, 2022)

Causal nexus in industrialization, urbanization, trade openness, and carbon emissions: empirical evidence from OPEC economies - Muhammad Azam; Zia Ur Rehman; Yusnidah Ibrahim (Environment, Development and Sustainability, 2022)

Assessment and source apportionment of water-soluble heavy metals in road dust of Zhengzhou, China - Muhammad Faisal; Zening Wu; Huiliang Wang; Zafar Hussain; Muhammad Imran Azam; Muhammad Muzammil (Environmental Science and Pollution Research, 2022)

Testing stationarity of per capita energy consumption across the globe: a better picture using the wavelet framework - Mumtaz Ahmed; Muhammad Azam; Atif Maqbool Khan (Environmental Science and Pollution Research, 2022)

Evaluating the impact of GDP per capita on environmental degradation for G-20 economies: Does N-shaped environmental Kuznets curve exist? - Abdul Majid Awan; Muhammad Azam (Environment, Development and Sustainability, 2022)

Performance evaluation and comparison of observed and reanalysis gridded precipitation datasets over Pakistan - Sayed Waseem Iqbal; Muhammad Latif; Rehan Ahmed; Shahzada Adnan; Muhammad Umar; Burhan Ahmad; Muhammad Azam; Jabir Hussain Syed (Theoretical and Applied Climatology, 2022)

Estimating the energy consumption function: evidence from across the globe - Muhammad Azam; Ali Gohar; Festus Victor Bekun (Environmental Science and Pollution Research, 2022)

ATP-binding cassette transporters expression profiling revealed its role in the development and regulating stress response in Solanum tuberosum - Madiha Zaynab; Zongkang Wang; Athar Hussain; Khalida Bahadar; Mateen Sajid; Yasir Sharif; Muhammad Azam; Kalsoom Sughra; Muhammad Ammar Raza; Khalid Ali Khan; Shuangfei Li (Molecular Biology Reports, 2022)

Does foreign direct investment limit trade-adjusted carbon emissions: fresh evidence from global data - Muhammad Azam; Ali Raza (Environmental Science and Pollution Research, 2022)

A comparative Appraisal of Classical and Holistic Water Scarcity Indicators - Zafar Hussain; Zongmin Wang; Jiaxue Wang; Haibo Yang; Muhammad Arfan; Daniyal Hassan; Wusen Wang; Muhammad Imran Azam; Muhammad Faisal (Water Resources Management, 2022)

Structural characterization and antileishmanial activity of newly synthesized organo-bismuth(V) carboxylates: experimental and molecular docking studies - Sohaila Andleeb; Imtiaz-ud-Din; Muhammad Khawar Rauf; Syed Sikander Azam; Ihsan‐ul Haq; Muhammad Nawaz Tahir; Naila Zaman (JBIC Journal of Biological Inorganic Chemistry, 2022)

A spreadsheet-based tool for optimal design of reinforced concrete cantilever retaining walls - Mansoor Shakeel; Rizwan Azam; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2022)

Characterization and thermal behavior of marble from northwestern Pakistan - Atta Ur Rehman; Waqas Ahmed; Shahid Azam; Muhammad Sajid (Innovative Infrastructure Solutions, 2022)

Mechanical and durability properties of fly-ash cement sand composite bricks: an alternative to conventional burnt clay bricks - Azaz Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mohamed Zawam (Innovative Infrastructure Solutions, 2022)

Production of bimodal molecular weight levan by a Lactobacillus reuteri isolate from fish gut - Waqar Ahmad; Anam Nasir; Fazal Sattar; Iram Ashfaq; Ming-Hsu Chen; Azam Hayat; Mujaddad ur Rehman; Sainan Zhao; Shazia Khaliq; Muhammad Afzal Ghauri; Munir Ahmad Anwar (Folia Microbiologica, 2022)

Climatology of dust storm frequency and its association with temperature and precipitation patterns over Pakistan - Mehwish Aziz Dar; Rehan Ahmed; Muhammad Latif; Muhammad Azam (Natural Hazards, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Integrated support vector regressor and hybrid neural network techniques for earthquake prediction along Chaman fault, Baluchistan - Umer Khalil; Bilal Aslam; Zaheer Abbas Kazmi; Ahsen Maqsoom; Muhammad Irshad Qureshi; Sheheryar Azam; Ahsan Nawaz (Arabian Journal of Geosciences, 2021)

Convective available potential energy (CAPE) in Pakistan and its association with precipitation and temperature - Sameen Malik; Rehan Ahmed; Muhammad Latif; Muhammad Azam; Ehsan Haroon; Muhammad Bilal Iqbal (Theoretical and Applied Climatology, 2021)

Evaluating the meteorological drought characteristics over Pakistan using in situ observations and reanalysis products - Irfan Ullah; Xieyao Ma; Jun Yin; Temesgen Gebremariam Asfaw; Kamran Azam; Sidra Syed; Mengyang Liu; Muhammad Arshad; Muhammad Shahzaman (International Journal of Climatology, 2021)
Drought is one of the most frequent natural disasters occurring in Pakistan and has a great influence on livelihood, agriculture, and economy. The availability of long‐term high‐quality reanalysis products over Pakistan has been of great concern in recent decades. Here, we conduct drought assessment in Pakistan based on the standardized precipitation index (SPI) and the standardized precipitation evapotranspiration index (SPEI) at 3, 6, and 12 months timescales during 1983–2018. We use long‐term in situ observations to evaluate the accuracy of reanalysis products, including Climatic Research Unit (CRU TS), National Centers for Environmental Prediction version II (NCEP‐2), European Centre for Medium‐Range Weather Forecasts Version‐5 (ERA‐5), and Modern‐Era Retrospective analysis for Research and Applications version II (MERRA‐2). The main results are summarized as follows: (a) drought indices and drought areas assessed from reanalysis products are relatively more representative of historical droughts that had occurred in southern Pakistan and overestimation is evident for drought severity in western than eastern Pakistan; (b) statistically significant increasing trends (1984–1998 and 2000–2010) in monthly drought areas and occurrence are evident by CRU TS and MERRA‐2 in dominant arid and semiarid regions; (c) climate variables and drought features of southern Pakistan are best represented by CRU TS and MERRA‐2, while that of southwestern and western parts are best represented by ERA‐5; (d) the Nash–Sutcliffe efficiency (NSE) results range from −2 to 1, where the NSE of SPEI values (−1.0) show relatively weaker than SPI values (0.5) in most parts of the regions, specifically in the southern Pakistan; (e) a strong positive linear relationship on a monthly scale is evident in CRU TS, MERRA‐2, and ERA‐5 exhibiting relatively high correlation coefficient (0.84), except for NCEP‐2. Furthermore, the SPEI results are found to be better than SPI; thus, this study suggests SPEI may be more suitable than SPI in monitoring droughts under climate change.

A spatial-temporal decomposition of carbon emission intensity: a sectoral level analysis in Pakistan - Muhammad Azam; Saima Nawaz; Zubair Rafiq; Nasir Iqbal (Environmental Science and Pollution Research, 2021)

P53-mediated in vitro inhibition of PhIP-induced oxidative damage by myricetin bulk and nano forms in healthy lymphocytes - Shabana Akhtar; Diana Anderson; Talha Muhammad Azam; Arif Malik (Archives of Toxicology, 2021)

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

Dynamic nexus among tourism, corruption, democracy and environmental degradation: a panel data investigation - Muhammad Haseeb; Muhammad Azam (Environment, Development and Sustainability, 2021)

Projected drought pattern under climate change scenario using multivariate analysis - Muhammad Waseem; Muhammad Ajmal; Ijaz Ahmad; Noor Muhammad Khan; Muhammad Azam; Muhammad Kaleem Sarwar (Arabian Journal of Geosciences, 2021)

Quantification of Climate Warming and Crop Management Impacts on Phenology of Pulses-Based Cropping Systems - Zartash Fatima; Atique-ur-Rehman; Ghulam Abbas; Pakeeza Iqbal; Iqra Zakir; Muhammad Azam Khan; Ghulam Mujtaba Kamal; Mukhtar Ahmed; Shakeel Ahmad (International Journal of Plant Production, 2021)

Impact of institutional quality on environment and energy consumption: evidence from developing world - Muhammad Azam; Liu Liu; Najid Ahmad (Environment, Development and Sustainability, 2021)

Inheritance of leaf resistance to Sclerotinia sclerotiorum in Brassica napus and its genetic correlation with cotyledon resistance - Muhammad Azam Khan; Wallace Cowling; Surinder Singh Banga; Ming Pei You; Vikrant Tyagi; Baudh Bharti; Martin J. Barbetti (Euphytica, 2020)

Does globalization and financial sector development affect environmental quality? A panel data investigation for the Middle East and North African countries - Abdul Majid Awan; Muhammad Azam; Imran Ullah Saeed; Baher Bakhtyar (Environmental Science and Pollution Research, 2020)

Changes in Soil Organic Carbon Fractions Across a Loess Toposequence - Arsalan Azam; Mohammad Saleem Akhtar; Shah Rukh; Ayaz Mehmood; Muhammad Imran; Ahmad Khan; Abdul Qayyum; Waseem Ahmad; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2020)

Patterns of inheritance for cotyledon resistance against Sclerotinia sclerotiorum in Brassica napus - Muhammad Azam Khan; Wallace Cowling; Surinder Singh Banga; Ming Pei You; Vikrant Tyagi; Baudh Bharti; Martin J. Barbetti (Euphytica, 2020)

Spatio-statistical analysis of rainfall fluctuation, anomaly and trend in the Hindu Kush region using ARIMA approach - Muhammad Dawood; Atta-ur Rahman; Sami Ullah; Shakeel Mahmood; Ghani Rahman; Kamran Azam (Natural Hazards, 2020)

Examining foreign direct investment and environmental pollution linkage in Asia - Muhammad Azam Khan; Ilhan Ozturk (Environmental Science and Pollution Research, 2020)

Glycinebetaine alleviates the chromium toxicity in Brassica oleracea L. by suppressing oxidative stress and modulating the plant morphology and photosynthetic attributes - Rehan Ahmad; Shafaqat Ali; Muhammad Abid; Muhammad Rizwan; Basharat Ali; Asif Tanveer; Irfan Ahmad; Muhammad Azam; Muhammad Awais Ghani (Environmental Science and Pollution Research, 2020)

Spatiotemporal trends in reference evapotranspiration over South Korea - Ju Ha Hwang; Muhammad Azam; Maeng Seung Jin; Yong Ho Kang; Jae Eun Lee; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Muhammad Zaffar Hashmi (Paddy and Water Environment, 2020)

Genome Wide Identification and Expression Profiles of TALE Genes in Pineapple (Ananas comosus L) - Hina Ali; Yanhui Liu; Syed Muhammad Azam; Imran Ali; Umair Ali; Weimin Li; Hafiza Javaria Ashraf; Yang Jie; Stefan Olsson; Yuan Qin (Tropical Plant Biology, 2019)

Effect of Methyl Jasmonate and Salicylic Acid on In Vitro Growth, Stevioside Production, and Oxidative Defense System in Stevia rebaudiana - Sajjad Moharramnejad; Amirali Taheri Azam; Jaber Panahandeh; Zahra Dehghanian; Muhammad Ashraf (Sugar Tech, 2019)

Relationship between energy, investment, human capital, environment, and economic growth in four BRICS countries - Muhammad Azam (Environmental Science and Pollution Research, 2019)

Proteome-wide subtractive approach to prioritize a hypothetical protein of XDR-Mycobacterium tuberculosis as potential drug target - Reaz Uddin; Quratulain Nehal Siddiqui; Muhammad Sufian; Syed Sikander Azam; Abdul Wadood (Genes & Genomics, 2019)

Bambara groundnut: an exemplar underutilised legume for resilience under climate change - Sean Mayes; Wai Kuan Ho; Hui Hui Chai; Xiuqing Gao; Aloyce C. Kundy; Kumbirai I. Mateva; Muhammad Zahrulakmal; Mohd Khairul Izwan Mohd Hahiree; Presidor Kendabie; Luis C. S. Licea; Festo Massawe; Tafadzwanashe Mabhaudhi; et al. (Planta, 2019)

Comparative effect of mesquite biochar, farmyard manure, and chemical fertilizers on soil fertility and growth of onion (Allium cepa L.) - Mumtaz Khan; Kaneez Fatima; Rehan Ahmad; Rafia Younas; Muhammad Rizwan; Muhammad Azam; Zain ul Abadin; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Carcass characteristics and serum biochemical profile of Japanese quail by the supplementation of pine needles and vitamin E powder - Irfan Ullah Khan; Assar Ali Shah; Fayaz Ahmed Sahibzada; Azam Hayyat; Mudasir Nazar; Muhammad Mobashar; Ambrina Tariq; Nighat Sultana (Biologia, 2019)

Virulence-associated genes and antimicrobial resistance among avian pathogenic Escherichia coli from colibacillosis affected broilers in Pakistan - Mariya Azam; Mashkoor Mohsin; Sajjad-ur-Rahman; Muhammad Kashif Saleemi (Tropical Animal Health and Production, 2019)

The effects of energy on investment, human health, environment and economic growth: empirical evidence from China - Muhammad Azam; Abdul Qayyum Khan; Ilhan Ozturk (Environmental Science and Pollution Research, 2019)

Hemp (Marijuana) reverted Copper-induced toxic effects on the essential fatty acid profile of Labeo rohita and Cirrhinus mrigala - Azam Jan Afridi; Amina Zuberi; Ali Muhammad Yousafzai; Maria; Muhammad Kamran; Sana Ullah (Molecular Biology Reports, 2019)

Synthesis and applications of nano-TiO2: a review - Muhammad Tayyab Noman; Muhammad Azeem Ashraf; Azam Ali (Environmental Science and Pollution Research, 2019)

Foliar- and soil-applied salicylic acid and bagasse compost addition to soil reduced deleterious effects of salinity on wheat - Muhammad Imran Khan; Muhammad Aqeel Shoukat; Sardar Alam Cheema; Shafaqat Ali; Muhammad Azam; Muhammad Rizwan; Rashad Qadri; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2019)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Spatio-temporal analysis of temperature variability, trend, and magnitude in the Hindu Kush region using Monte Carlo and Sen’s slope approaches - Muhammad Dawood; Atta-ur Rahman; Sami Ullah; Ghani Rahman; Kamran Azam (Arabian Journal of Geosciences, 2018)

Identification, Characterization and Expression Profiles of Dof Transcription Factors in Pineapple (Ananas comosus L) - Syed Muhammad Azam; Yanhui Liu; Zia Ur Rahman; Hina Ali; Cheng Yan; Lulu Wang; S. V. G. N. Priyadarshani; Binyan Hu; Xinyu Huang; Junjie Xiong; Yuan Qin (Tropical Plant Biology, 2018)

Nucleosomes positioning around transcriptional start site of tumor suppressor (Rbl2/p130) gene in breast cancer - Farman Ullah Farman; Mehwish Iqbal; Muhammad Azam; Muhammad Saeed (Molecular Biology Reports, 2018)

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Genome-Wide Identification of Auxin Response Factor (ARF) Genes Family and its Tissue-Specific Prominent Expression in Pineapple (Ananas comosus) - Zhenxia Su; Lulu Wang; Weimin Li; Lihua Zhao; Xinyu Huang; Syed Muhammad Azam; Yuan Qin (Tropical Plant Biology, 2017)

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress - Mujahid Farid; Shafaqat Ali; Muhammad Rizwan; Rashid Saeed; Hafiz Muhammad Tauqeer; Rasham Sallah-Ud-Din; Ahmed Azam; Nighat Raza (Environmental Science and Pollution Research, 2017)

Growth-corruption-health triaca and environmental degradation: empirical evidence from Indonesia, Malaysia, and Thailand - Muhammad Azam; Abdul Qayyum Khan (Environmental Science and Pollution Research, 2017)

The dynamic relationship between structural change and CO2 emissions in Malaysia: a cointegrating approach - Wajahat Ali; Azrai Abdullah; Muhammad Azam (Environmental Science and Pollution Research, 2017)

The impact of CO2 emissions on economic growth: evidence from selected higher CO2 emissions economies - Muhammad Azam; Abdul Qayyum Khan; Hussin Bin Abdullah; Muhammad Ejaz Qureshi (Environmental Science and Pollution Research, 2016)

Environment and air pollution like gun and bullet for low-income countries: war for better health and wealth - Xiang Zou; Muhammad Azam; Talat Islam; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Causal nexus between energy consumption and carbon dioxide emission for Malaysia using maximum entropy bootstrap approach - Sehrish Gul; Xiang Zou; Che Hashim Hassan; Muhammad Azam; Khalid Zaman (Environmental Science and Pollution Research, 2015)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Environmental quality indicators and financial development in Malaysia: unity in diversity - Arif Alam; Muhammad Azam; Alias Bin Abdullah; Ihtisham Abdul Malik; Anwar Khan; Tengku Adeline Adura Tengku Hamzah; Faridullah; Muhammad Mushtaq Khan; Hina Zahoor; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Hydrogen sulfide alleviates the aluminum-induced changes in Brassica napus as revealed by physiochemical and ultrastructural study of plant - Basharat Ali; Ping Qian; Rui Sun; Muhammad A. Farooq; Rafaqat A. Gill; Jian Wang; Muhammad Azam; Weijun Zhou (Environmental Science and Pollution Research, 2015)

Erratum to: Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Estrus response and follicular development in Boer does synchronized with flugestone acetate and PGF2α or their combination with eCG or FSH - Muhammad Modu Bukar; Rosnina Yusoff; Abd Wahid Haron; Gurmeet Kaur Dhaliwal; Mohd Azam Goriman Khan; Mohammed Ariff Omar (Tropical Animal Health and Production, 2012)

Molecular simulations of bergenin as a new urease inhibitor - Mohammad Arfan; Hazrat Amin; Inamullah Khan; Muhammad Raza Shah; Hamidullah Shah; Amir Zada Khan; Syed Muhammad Ashhad Halimi; Nematullah Khan; Waqar Ahmad Kaleem; Mughal Qayum; Adnan Shahidullah; Muhammad Azam Khan (Medicinal Chemistry Research, 2012)

Novel and recurrent LDLR gene mutations in Pakistani hypercholesterolemia patients - Waqas Ahmed; Muhammad Ajmal; Ahmed Sadeque; Roslyn A. Whittall; Sobia Rafiq; Wendy Putt; Athar Khawaja; Fauzia Imtiaz; Nuzhat Ahmed; Maleeha Azam; Steve E. Humphries; Raheel Qamar (Molecular Biology Reports, 2012)

A missense mutation (p.G274R) in gene ASPA causes Canavan disease in a Pakistani family - Rashida Hussain; Shakeela Daud; Naseebullah Kakar; Adeel Ahmad; Abdul Hameed Baloch; Abdul Malik Tareen; Muhammad Azam Kakar; Jamil Ahmad (Molecular Biology Reports, 2012)

In vitro selection of resistant mutant garlic lines by using crude pathogen culture filtrate of Sclerotium cepivorum - Lin-qing Zhang; Zhi-hui Cheng; Muhammad Azam Khan; Yan-li Zhou (Australasian Plant Pathology, 2012)

DNA typing of Pakistani cattle breeds Tharparkar and Red Sindhi by microsatellite markers - Amber Azam; Masroor Ellahi Babar; Sehrish Firyal; Aftab Ahmad Anjum; Nabeela Akhtar; Muhammad Asif; Tanveer Hussain (Molecular Biology Reports, 2012)

Role of tissue plasminogen activator and plasminogen activator inhibitor polymorphism in myocardial infarction - Waqas Ahmed; Meera Malik; Imran Saeed; Amina Ali Khan; Ahmed Sadeque; Umar Kaleem; Nuzhat Ahmed; Muhammad Ajmal; Maleeha Azam; Raheel Qamar (Molecular Biology Reports, 2011)

Design, construction and performance evaluation of small tile drainage systems in the Indus Basin - Muhammad Akram Kahlown; Muhammad Khan Marri; Muhammad Azam (Irrigation and Drainage, 2007)

Individual and combined effect of waterlogging and salinity on crop yields in the Indus basin - Muhammad Akram Kahlown; Muhammad Azam (Irrigation and Drainage, 2002)
Waterlogging and salinity are the major threats to the sustainability of irrigated agriculture in Pakistan. About 50% of the Culturable Command Area (CCA) in the Fordwah Eastern Sadiqia South (FESS) is affected by waterlogging and 12% by surface and profile salinity. A sample of 26 watercourses was selected in the project area to evaluate the individual and combined impacts of waterlogging and salinity on the yields of cotton, wheat, sugarcane and rice. The crop yields were measured separately for waterlogged fields and those affected with salinity and waterlogging simultaneously. The extent of yield loss as result of a rise in the water table from 1–2 m to less than 1 m was 27 and 33% for wheat and sugarcane crops, whereas it was 7 and 6% in the case of a drop of the water table to more than 2 m. For cotton, a rising water table from 2–3 m to 1–2 m and less than 1 m gave a yield decrease of about 11 and 60% respectively. The rice crop preferred waterlogging, and in contrast to other crops, gave about 7% less yield with a lowering of the water table from less than 1 m to 1–2 m. The wheat and sugarcane yields had decreasing trends with salinity in excess of 4 dS m −1 and had complete failures with salinity greater than 12 dS m −1 at water table depths of less than 1, 1–2 and 2–3 m. The cotton crop demonstrated relatively higher salinity tolerance under a water table deeper than 1 m. However, this crop could not survive at salinity levels in excess of 12 dS m −1 at water table depth of less than 1 m. The rice crop was a complete failure at salinity level of greater than 12 dS m −1 under water table depths of less than 1 and 1–2 m. The combined impact of waterlogging and salinity was more harmful to crop yields when compared with the individual effects of waterlogging. The combined analysis of waterlogging and salinity on crop yields provide a good sensitivity of the salinity‐yield relationships and indicated the importance of subsurface drainage. Copyright © 2002 John Wiley & Sons, Ltd.

Fate and Interaction with Soil N of Fertilizer 5N Applied to Wheat at Different Growth Stages - Muhammad Ashraf; Farooq-e-Azam (Cereal Research Communications, 1998)